Students’ Involvement in EFL online classroom during Covid-19 Pandemic at Senior High School - Isna, Nur Isnani (Technium Social Sciences Journal, 2021)
According to Norziani Dahalan, (2012) students’ involvement is important in online classes. When students communicate verbally with teachers or with friends, their abilities will automatically develop. However, in online classes the researcher found that students were passive and didn't want to calculate their progress, they would be slower. Therefore, this study aims to see how the students’ involvement in EFL online classroom during Covid-19 Pandemic at State Senior High School 1 Bengkalis with the hope that teachers can try to overcome it. This type of research is descriptive qualitative research. To measure the data, researchers used observation, video documentation, and interviews. The data analysis technique used in this research is to use qualitative data analysis techniques developed by Miles, (2019) which includes three activities, namely: data reduction, data presentation, concluding, or levers. The results of this study are: First, student involvement with the teacher is passive. Second, student involvement with other students. Students can interact with their classmates in the online learning process even though the response is very time-consuming because the teacher or student's internet connection network is sometimes bad and interferes with the learning process. Third, student involvement with the material. The involvement of English students with learning materials at SMA N 1 can be said to be good. Because the English teacher teaches well like how he does face-to-face learning in class. The difference is, he uses an online application.